AB0769 Lipid Characterization of Chondrogenic Differentiation Using Maldi Mass Spectrometry Imaging. (10th June 2014) - Rocha, B.; Cillero-Pastor, B.; Eijkel, G.; Ruiz-Romero, C.; Heeren, R.M.; Blanco, F.J.
Abstract : Background: Recent investigations have argued that there is a close relationship between altered lipid metabolism and Osteoarthritis (OA) disease. Mesenchymal stem cells (MSC) are an interesting alternative for cell-based therapy of cartilage defects due to their capacity to differentiate towards chondrocytes in a process called chondrogenesis. The knowledge of the lipid distribution and modulation during this process could be used to improve the MSC-based cartilage therapy by the discovery of new chondrogenic markers. Objectives: To characterize the lipid profiles of 3D MSC cultures (micromasses) at different time points of chondrogenesis using matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI). Methods: MSC micromasses obtained from the bone marrow of 3 OA donors were collected at day 2 and 14 of chondrogenesis and studied in duplicate. Samples were cut in sections of 10 μm thickness and dried in a vacuum desiccator for 20 min to prevent the molecular delocalization. Two matrix solutions were prepared (Alpha-cyano-4-hydroxycinnamic acid at 10 mg/ml in 70:30 methanol:trifluoroacetic acid 0.2%; 9-Aminoacridine at 10 mg/ml in 70:30 ethanol:water) and applied on the surface of the tissue slides using a vibrational sprayer (ImagePrep, Bruker, Germany). MALDI-MSI was performed using a MALDI-Q-TOF instrument (Synapt HDMS, Waters, UK) equipped with a 200-Hz Nd:YAG laser. Data were acquired in the mass/charge (m/z) range of 100-1000 and at a raster size of 100 μm (positive and negative V-reflectron mode). Ion images were generated with Biomap 3.7.5.5 software. Principal component analysis (PCA) and discriminant analysis (DA) were used to look for the masses with the highest differences between all samples studied. Finally, tandem mass spectrometry (MS/MS) was carried out to identify these masses. Lipid assignments were performed according to literature and LIPID MAPS Structure Database (LMSD). Results: MALDI-MSI revealed a differential lipid profile between the two time points (2 and 14 days). Firstly, we analyzed the lipid composition in the positive mode. The analysis of 683 spectra by statistical methods such as PCA and DA showed a higher lipid content at day 2 of chondrogenesis. According to Lipidmaps database and MS/MS fragmentation, these peaks are attributed to phosphocholine (m/z 184) and several phosphatidylcholines (PC) (m/z 739.5, m/z 798.5 and m/z 826.6). Other differentially expressed peaks could be assigned to sphingomyelines (SM) (m/z 725.5, m/z 741.5, m/z 767.5 and m/z 826.6). Only m/z 729.5, m/z 756.5 and m/z 790.5 were increased at day 14, corresponding to SM and two PCs, respectively. For the negative mode 745 spectra were used. The first discriminant function revealed a high presence of phosphatidylinositols (PI) (m/z 885.6) and phosphatidyletanolamines (PE) such as m/z 750.5 specifically at day 14. Biomap software confirmed the results obtained by PCA and DA. Conclusions: These data demonstrate that MALDI-MSI can be used for the identification of putative chondrogenic markers. We have observed that the lipid metabolism is involved in the chondrogenic process. Phosphatidyletanolamine and phosphatidylinositol pathways are increased in chondrocyte-differentiated MSC, whereas phosphocholine-related lipids could be markers of the undifferentiated stage. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5012